The impact of different road disturbances on farm gate, wholesale and retail prices of selected food commodities in Metro Manila - Barnedo, Charlotte A.; Famero, Marie Carolaine C.; Reside, Renato Jr. E. (Quezon City School of Economics, University of the Philippines Diliman, 2018)
The authors of this study are just two of the hundreds of thousands of Filipinos who experience aggravating traffic in Metro Manila. This has led them to be interested on conducting a study which seeks to explore the probable impact of traffic congestion on today_s economy. Because of the vast range of economic factors that traffic can tackle, the authors chose to narrow it down to food commodity prices in the capital region. Surprisingly, there are no existing studies regarding this matter which challenged them to find and analyze appropriate related literature for this study. The panel dataset contains quarterly observations between 2010_2017 of food prices (i.e. farm gate, wholesale, retail), gross regional domestic product (GRDP), volume of production, Annual Average Daily Traffic (AADT) and frequency of disasters. The authors were able to obtain the said statistics from Philippine Statistics Authority (PSA), Department of Public Works and Highways (DPWH) and Centre for Research on the Epidemiology of Disasters (CRED), respectively. To widen the scope of this study, the authors expanded the predicting factor, traffic congestion, into different road disturbances. In line with this, natural disasters were added since intuition suggests that its occurrence and effects can be considered a road disturbance. Moreover, studies suggest that it can also affect commodity prices. With these in mind, the study_s main objective is to test the impact of different road disturbances mentioned, on food prices in Metro Manila. Random effects model was used since this study suggests the use of a panel dataset containing data on prices, regional GDP, and measures of natural disasters and traffic congestion. Through this model, it was determined that different road disturbances indeed significantly affect prices in various provinces. However, these effects vary on the type of commodity coming from different top_producing supplier provinces.
Thesis (B.S. Business Economics) -- University of the Philippines Diliman
Keywords: Traffic congestion -- Economic aspects -- Philippines -- Metro Manila; Food prices -- Philippines -- Metro Manila